INFORMATION TECHNOLOGIES IN THE DEVELOPMENT OF WEB RESOURCES - KRAVCHUK, OLHA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article focuses on an overview, analysis and examples of the use of information technology in the development of web resources. Information technology is a field of knowledge and practical applications related to the collection, processing, storage, transmission and use of information using computer systems. Information technology is used in various industries, such as business, medicine, education, science, entertainment, and many others. Information technology covers a wide range of technologies, including software, hardware, networks, and other tools that help in managing information. They are used at every stage of web resource development, from design to deployment and support. The article describes the key aspects of IT: programming languages and frameworks; databases that can be used to store information on a web server, as well as to provide access to data through web applications using programming languages and frameworks; web servers and hosting; version control systems that help developers effectively manage code and work together on projects of any complexity; security (ensuring the security of web resources includes the use of encryption methods, data validation, protection against Testing and debugging are iterative processes that are repeated throughout the development cycle to ensure the quality and reliability of a web application). They can be used to automate business processes, increase productivity, ensure data security, simplify communication, and provide access to information.